Re-evaluation of coastal cultural heritage resources : case study of North Carolina southeastern coastal region - Khakzad, Sorna (East Carolina University, 2016)
Humans have had a long history of interconnectedness with the sea and ocean due to the use of natural resources available in the coastal areas. These interactions have influenced the natural landscape and played a crucial role in the formation of coastal cultural heritage. Coastal cultural heritage, a continuum of land and sea, is an important part of our cultural resources in the coastal areas. Presently, coastal cultural heritage has not been well-integrated into coastal management plans as a cultural resource. the values of cultural heritage have theoretically been recognized in benefiting people and its role in sustainable development. However, the qualitative and comparative analysis of coastal management experiences show that many valuable cultural heritage assets have been overlooked as resources in coastal management schemes. Acknowledging the significance of cultural heritage in Brunswick Country coastal area, the current study address three topics: 1) assessment of the impact of natural and environmental factors on coastal cultural heritage and identifying the heritage items that have been marginalized for variety of different reasons; 2) considering a new evaluation of a selected marginalized cultural heritage (fishing cultural heritage) and assessing the role of cultural heritage for fishing communities wellbeing; and 3) finally exploring the feasibility of developing a cultural tourism in Brunswick County directed at fishing communities. The study applies a multidisciplinary approach for data collection, analysis and evaluation purposes. A synthesis approach is applied and data from different sources on cultural and archaeological resources, and natural-environmental factors are compiled. ArcGIS software is used for analyzing data and creating risk maps for cultural heritage. In addition, several interviews and photo elicitation methods are used for understanding the viewpoints of local fishing communities regarding their cultural heritage resources. Content analysis, a series of graphs and quantitative analysis are applied to understand the state of cultural tourism in Brunswick County on fishing communities. The result of the first part of study shows that there are several sites that are in potential risk zones. However, more site-specific data are required for better assessment. The second section concluded that fishing communities respect their material culture. There are sites, buildings and objects related to fishing that are of sociocultural significance for fishing communities in Brunswick County. However, many of these items are suffering lack of attention and also abandonment. The study on tourism revealed that although there is interest in visiting fishing heritage, lack of information and proper publicity on fishing cultural heritage resulted in overlooking fishing cultural heritage sites as a tourist attraction. The study concludes that a balanced integrated and interdisciplinary evaluation of different cultural resources can enhance our understanding of the holistic values of cultural heritage as a resource to benefit people. Passing this understanding to managers and policy makers will help to improve future planning aimed at sustainable development. Better decisions require concrete evidence that demonstrates how re-evolution of cultural capital in regards to different aspects of communities and society can lead to outcomes that improve human well-being in the short and long term. This evidence should combine natural-environmental, cultural, economic, and social data.
Keywords: Coastal zone management--North Carolina-- Brunswick County; Cultural property--North Carolina--Brunswick County; Fishers--North Carolina--Brunswick County